Evaluation of the effects of intravenous lipid emulsion and ethanol on the optic nerve and retina in methanol-intoxicated rats: a histopathological study - Can, Muhammet; Yildirim, Humeyra; Bulmus, Ozgur; Turan, Gulay; Gokbulut, Cengiz; Hismiogullari, Adnan Adil; Yaranoglu, Mustafa Hilmi (The Bulletin of Legal Medicine, 2025)
Objective: This study aimed to evaluate the therapeutic efficacy of intravenous lipid emulsion (ILE) compared with ethanol in the treatment of optic neuropathy induced by acute methanol intoxication in rats.Methods: Sixty-four male rats were divided into seven groups: Group 1 (control), Group 2 (methanol), Group 3 (methanol + ethanol), Group 4 (methanol + ILE), Group 5 (methanol + ethanol + ILE), Group 6 (ethanol), and Group 7 (ILE). Blood samples were collected to assess liver and kidney functions. After sacrifice, the optic nerve and retina were examined histologically.Results: The combination of methanol, ethanol, and ILE improved LDH and CK-MB levels. Histopathological analysis revealed marked vascularization and vacuolization in the optic nerve of the methanol group, whereas these changes were minimal in the methanol + ethanol + ILE group. Neither ILE nor ethanol caused significant apoptotic alterations in the retina (p = 0.357). Pronounced edema, vascularization, apoptotic changes, and vacuolization were observed in the methanol group, but these effects were largely absent in the methanol + ILE and methanol + ethanol + ILE groups compared with controls.Conclusion: The combined administration of ethanol and ILE exerts a protective effect against methanol-induced cardiac and optic nerve damage. Histopathologically, this combination mitigates the degenerative effects of methanol on both the optic nerve and retinal tissues.
Keywords: methanol intoxication; ethanol; intravenous lipid emulsion; optik nerve; Retina